Clinical characteristics and prognosis of interstitial lung disease in systemic juvenile idiopathic arthritis: a two-center retrospective observational cohort study - Wenting Zhan; Jinxiang Yang; Lingzhi Qiu; Kangkang Yang; Xiaohua Ye; Yaoyao Shangguan; Haiguo Yu; Wenjie Zheng (BMC, 2024)
Abstract Background Interstitial lung disease (ILD) is a serious complication in systemic juvenile idiopathic arthritis (SJIA). This study aimed to identify the clinical characteristics and prognosis of SJIA-ILD. Methods A two-center retrospective cohort study was conducted on patients newly diagnosed with SJIA in China from October 2010 to December 2021. Clinical characteristics, laboratory parameters, outcomes, and relapse rates were compared between ILD and non-ILD groups. Results A total of 176 children with SJIA were included, including 35 in ILD group and 141 in non-ILD group. The median age at onset of SJIA was 5.8 years (range 4.4-9.5) in patients with SJIA-ILD. It exhibited higher incidences of cervical spine (28.6%) and hip involvement (40.0%) in ILD group (P = 0.031 and P = 0.029, respectively). The incidence of macrophage activation syndrome (MAS) in ILD group reached up to 40%, significantly elevated than that in non-ILD group (P = 0.047). Children with ILD demonstrated a stronger inflammatory response and were more prone to developing lymphopenia (P = 0.009), requiring more combination therapy (P = 0.006) to control disease activity. 54.3% of patients received biologic therapies, with only three patient receiving biologics (one with IL-6 blockade, two with TNF inhibitor) prior to ILD onset and none receiving IL-1 blockade. The median follow-up duration was 6.0 years (range 3.9-9.5). The proportions of patients with SJIA-ILD achieving clinical inactive disease without glucocorticoids within 6 to 12 months of the treatment were significantly lower than control group (45.7% vs. 70.2%, P = 0.006). In ILD group, only 54.3% of patients achieved complete remission, and 17.1% were in a non-remission state, among whom two deaths from respiratory failure. There was no significant difference in disease relapse rates between the two groups (P > 0.05). Conclusions Patients with SJIA-ILD exhibited heightened inflammation, increased hip joint and cervical spine involvement, and were more susceptible to developing lymphopenia and MAS, suggesting a relatively poor prognosis. They required a prolonged time to control inflammation and more aggressive treatment strategies to achieve inactive status. The unsatisfactory rate of complete remission highlighted an urgent need for focused clinical strategies.